SISTEM PAKAR DIAGNOSA KERUSAKAN SEPEDA MOTOR YAMAHA MATIC MENGGUNAKAN METODE FORWARD CHAINING - Asep Syaputra; Dedi Setiadi (Jusikom : Jurnal Sistem Komputer Musirawas, 2020)
The expert system is a computer-based system that uses knowledge, facts, and reasoning techniques to solve problems that usually only experts in their field can solve. The development of an expert system is aimed to help Yamaha motorbike users to solve damage problems to a Yamaha Automatic motorcycle. Damage to a Yamaha Automatic motorcycle is a problem that requires experts (technicians) to rely on their knowledge to solve the problem. This system is built using the forward chaining method which is used to test the factors that have been entered by using the rules stored in the system until a conclusion is obtained. By using the forward chaining method, it is hoped that it can help the system in diagnosing the damage to the Yamaha Automatic motorcycle engine. Therefore, by applying an expert system for motorcycle engine damage, the problem of Yamaha Automatic motorcycle engine damage can be resolved.